Initial Poor Graft Dysfunction and Primary Graft Non-Function After Orthotopic Liver Transplantation - Hao, Chen; Junjie, Xie; Baiyong, Shen; Xiaxing, Deng; Ran, Tao; Chenghong, Peng; Hongwei, Li (IntechOpen, 2011)
None